Genomic complexity in pediatric synovial sarcomas (Synobio study): the European pediatric soft tissue sarcoma group (EpSSG) experience. (13th March 2018) - Orbach, Daniel; Mosseri, Véronique; Pissaloux, Daniel; Pierron, Gaelle; Brennan, Bernadette; Ferrari, Andrea; Chibon, Frederic; Bisogno, Gianni; De Salvo, Gian Luca; Chakiba, Camille; Corradini, Nadège; Minard‐Colin, Véronique; et al.
Abstract: A genomic index (GI) tool using array comparative genomic hybridization (aCGH) on tumor cells has emerged as independent prognostic factor associated with the risk of metastatic relapse in synovial sarcoma (SS). The aim was to assess GI in pediatric patients with SS, to determine its value as a prognostic factor. All pediatric/adolescent/young adults' (<25 years) with localized SS prospectively included in the European EpSSG‐NRSTS05 protocol with a contributive aCGH were selected. Definition of GI was A 2 / C, where A is the total number of alterations (segmental gains and losses) and C is the number of involved chromosomes on aCGH results. GI1 group corresponds to cases with no copy number alterations (flat profile, GI = 0) and GI2 group cases with at least one or more copy number alterations (rearranged profile; GI ≥ 1). Samples were available from 61 patients. The median age of the cohort was 13 years (range: 4–24). Overall, 55.7% were GI1 group, and 44.3% GI2 . After a median follow‐up of 62 months (range: 0.1–112), 10 tumor events occurred and five patients died. Respectively, for GI1 versus GI2 groups, five‐year event‐free survival (EFS) was 93.8 ± 4.2% versus 64.9 ± 10.1% ( P  < 0.006) and five‐year Metastatic‐Free Survival (MFS) 93.8 ± 4.2% versus 72.9 ± 9.5% ( P  < 0.04). In multivariate analysis, GI status as adjusted for IRS group, patient age, site, and tumor size remain independent prognostic for EFS with a relative risk (RR) of 6.4 [1.3–31.9] ( P  < 0.01) and RR for MFS is 4.8 [0.9–25.7] ( P  < 0.05). Genomic complexity evaluated through GI may explain the metastatic behavior of pediatric SS. Abstract : This study analyzes 61 pediatric/adolescent/young adults (<25 years) with localized synovial sarcoma prospectively enrolled in the European EpSSG‐NRSTS05 protocol to demonstrate that somatic genomic index (GI) analyzed using comparative genomic hybridization had a high prognostic value in pediatric synovial sarcoma as an independent prognostic factors. It demonstrates that patients with tumor harboring high GI had worse five‐year event‐free and metastatic‐free survivals comparing to ones with no genomic instability, and that therefore GI could be used to stratify more accurately patients in the future.